Anti-inflammatory activity of raw and processed stingless bee honey - Chong, Kar Yeen; Chin, Nyuk Ling; Yusof, Yus Aniza; Fakurazi, Sharida (Rynnye Lyan Resources, 2021)
The anti-inflammatory activity of raw and processed Kelulut stingless bee honey was investigated for its ability to inhibit nitric oxide (NO) production in lipopolysaccharidestimulated RAW 264.7 cells. Raw honey was optimally processed by thermal processing and thermosonication at 90°C. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) cell viability assay showed that Kelulut honey from 7.8 to 500 µg/mL was not cytotoxic to RAW 264.7 cells as it resulted in at least 80% viable cells after 24 hr. Both raw and processed honey from 10 to 300 µg/mL displayed an increase and decrease in NO concentrations, suggesting a mixed effect of NO inhibition and enhancement. Maximum NO inhibition of 17.5% was recorded from 20 µg/mL of thermally processed honey while the highest NO enhancement of 7.8% was from 10 µg/mL of thermosonicated honey. The NO effects were independent of honey concentration and processing techniques, suggesting its potential robustness in medicinal properties as part of the diet.